Phosphorus fractions in apple orchards in Southern Brazil - Schmitt D.E.* (2017)
© 2017, Instituto Agronomico. All Rights Reserved.Phosphorus (P) applications at dosages higher than the necessary may cause P buildup in the soil labile fractions and, consequently, pollution of water sources. This study aimed to assess accumulation of P fractions as well as the parameters of adsorption isotherms in soil profiles having a history of application of phosphate fertilizers and cultivated with apple trees. Soil samples were collected from an area with no history of cultivation and 2 apple orchards cultivated for 8 (P8) and 18 (P18) years, in the city of Urubici, Santa Catarina, southern Brazil. Soil samples were air dried, sieved in a 2-mm mesh, and subjected to chemical analyses (P adsorption) besides P chemical fractionation. Applications of phosphate fertilizers to the orchards, particularly P18, increased the inorganic and organic concentrations of P in all fractions. The distribution of P in organic and inorganic forms in the planted soils was similar to the distribution observed for the native vegetation soil. The highest inorganic labile P fraction, the lowest maximum P adsorption capacity, and the highest equilibrium concentration values at P18 are indicators of a higher environmental pollution risk of the orchards soils compared to the native soil.